A small molecule compound IX inhibits telomere and attenuates oncogenesis of drug‐resistant leukemia cells. Issue 7 (20th May 2020) - Li, Yinghui; Gu, Jiali; Ding, Yahui; Gao, Huier; Li, Yafang; Sun, Yue; He, Mei; Zhang, Wenshan; Yin, Jingjing; Bai, Cuigai; Gao, Yingdai
Abstract: Drug resistance is a common obstacle in leukemia treatment and failing to eradicate leukemia stem cells is the main cause of leukemia relapse. Previous studies have demonstrated that telomerase activity is associated with deregulated self‐renewal of leukemia stem cells (LSCs). Here, we identified a novel compound IX, an imatinib derivative with a replacement fragment of a telomerase inhibitor, which can effectively eradicate LSCs but had no influence on normal hematopoietic stem cells (HSCs) survival. We showed that compound IX can decrease the viability of drug‐resistant K562/G cells and blast crisis CML primary patient cells. Besides, IX can affect LSC survival, inhibit the colony‐forming ability, and reduce LSC frequency. In vivo results showed that IX can relieve the tumor burden in patient‐derived xenograft (PDX) model and prolong the lifespan. We observed that compound IX can not only decrease telomerase activity, but also affect the alternative lengthening of telomeres. In addition, IX can inhibit both the canonical and non‐canonical Wnt pathways. Our data suggested this novel compound IX as a promising candidate for drug‐resistant leukemia therapy.